Peran Warmth, Gregariousness, Assertiveness, Activity Level, Excitement Seeking dan Positive Emotions dalam Merefleksikan Kepribadian Extraversion - Pipih Muhopilah; Fatwa Tentama; Yuzarion Yuzarion (Jurnal Psikologi Teori dan Terapan, 2021)
Extraversion personality is one of the personality dimensions in the big five pesonality. The extraversion personality is reflected in six aspects, namely warmth, gregariousness, assertiveness, activity level, excitement seeking and positive emotions. The purpose of this study was to examine the construct validity and construct reliability on the extraversion personality scale as well as to examine the aspects and indicators that reflect the construct of extraversion personality. The population in this study were all students of class VIII at schools X, Y, Z which are state junior high schools in Yogyakarta with a total of 524 students. The sample in this study is 185 students. The sampling technique uses cluster random sampling. The data collection method used extraversion personality scale. Research data were analyzed using Structural Equation Modeling (SEM) through the SmartPLS 3.2.8 program. Based on the results of the data analysis, the aspects and indicators that reflect the extraversion personality construct are valid and reliable. The most dominant aspect that reflects extraversion personality is the activity level with a loading factor of 0,764. Meanwhile, the weakest aspect in reflecting extraversion personality is warmth with a loading factor value of 0,424. These results indicate that all aspects and indicators are able to reflect the extraversion personality construct. Thus, the measurement model can be accepted because the theory describes the personality construct of extraversion fit with empirical data obtained from the subject.Keywords: Activity level, extraversion personality, warmthAbstrak: Kepribadian extraversion adalah salah satu dimensi kepribadian dalam big five pesonality. Kepribadian extraversion direfleksikan melalui enam aspek yaitu warmth, gregariousness, assertiveness, activity level, excitement seeking dan positive emotions. Tujuan penelitian ini adalah untuk menguji validitas konstruk dan reliabilitas konstruk pada skala kepribadian extraversion serta menguji aspek-aspek dan indikator-indikator yang dapat merefleksikan konstruk kepribadian extraversion. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII pada sekolah X, Y, Z yang merupakan sekolah menengah pertama negeri di Yogyakarta dengan jumlah 524 siswa. Sampel dalam penelitian ini berjumlah 185 siswa. Teknik sampling menggunakan cluster random sampling. Metode pengumpulan data menggunakan skala kepribadian extraversion. Data penelitian dianalisis dengan Structural Equation Modeling (SEM) melalui program SmartPLS 3.2.8. Berdasarkan hasil analisis data, diperoleh  hasil  aspek-aspek dan  indikator  yang merefleksikan konstruk  kepribadian extraversion dinyatakan valid dan reliabel. Aspek yang paling  dominan merefleksikan kepribadian extraversion adalah activity level dengan loading factor 0,764. Sedangkan aspek yang paling lemah dalam merefleksikan kepribadian extraversion adalah warmth dengan nilai loading factor 0,424. Hasil tersebut menunjukkan bahwa semua aspek dan indikator mampu merefleksikan konstruk kepribadian extraversion. Dengan demikian, model pengukuran bisa diterima karena teori yang menggambarkan konstruk kepribadian extraversion fit dengan data empirik yang diperoleh dari subjek.